Science and Society - What is Scientists’ return to the Society: Round Table of the DOBA Business School, Maribor, 9. 12. 2015 - Ovin, Rasto (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
After almost 25 years of independence it is high time to assess the the universities’ top researches’ contribution to a better every day living of the home population. The promotion system is heavily concentrated on publishing top research abroad. Here absent is the mission of top researchers to perform as a members of a society thus enabling minimum return of investment by the society. Therefore the DOBA Business School had on December 12th 2015 organized a round table: Science and Society – What is Scientists’ return to the Society? Participants at the round table were: • Peter Gabrijelčič, Dean, Faculty of Architecture, University of Ljubljana, • Dr. Lea Bregar, DOBA Business School, • Dr. Boris Cizelj, DOBA Business School and Slovenian Innovation Hub Ljubljana, • Jasna Dominko Baloh, Director of the DOBA Group, • Andrej Fištravec, Mayor of City of Maribor, • Dr. Alojz Križman, Former Rector of the University of Maribor and Former Mayor of City of Maribor, • Anton Habjanič, Director of TehnoCenter at the University in Maribor, • Dr. Željko Knez, Faculty of Chemistry and Chemical Technology at the University of Maribor, • Slavka Marinič, CEO, Primat d.o.o., • Dušan Merc, prof., Headmaster of Prule Elementary School Ljubljana, • Dr. Rasto Ovin, Dean of the DOBA Business School, • Miro Puhek, DOBA Business School, Maribor • Dr. Ludvik Toplak, Director of the Alma Mater Europea and Former Rector of the University of Maribor, and • Ddr. Ana Vovk Korže, Faculty of Phylosophy, University of Maribor.